Cloud thermodynamic phase detection using a directional polarimetric camera (DPC). (September 2020) - Shang, Huazhe; Letu, Husi; Chen, Liangfu; Riedi, Jérôme; Ma, Run; Wei, Lesi; Labonnote, Laurent C.; Hioki, Souichiro; Liu, Chao; Wang, Zhongting; Wang, Jianjie
Highlights: The polarized cloud phase (P-CP) algorithm is developed for DPC. CALIPSO is used to reliably select DPC pixels containing liquid or ice clouds. Validation of P-CP against POLDER and MODIS global products are shown. Abstract: Cloud phase detection via satellites is essential in the accurate estimation of cloud radiative forcing at global and regional scales. The difference in polarized reflectance features between liquid and ice clouds can be used for detecting the cloud phase. The directional polarimetric camera (DPC) onboard the Chinese GaoFen-5 satellite was launched in May 2018. The multidirectional, multispectral, and multipolarization capabilities of the DPC provide essential measurements to better understand the distribution of clouds and their physical properties. Numerous studies have demonstrated that the angular polarization signatures of ice crystals and liquid cloud droplets are effective in the detection of liquid and ice clouds. This study uses cloud phase profiles from Cloud Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) to select reliable liquid and ice cloud pixels via the DPC and analyzes the angular polarization signatures of ice and cloud clouds. These extracted angular polarization signatures are compared with the simulated results. Then, based on the earlier POLDER cloud phase algorithm, we propose a cloud phase detection method (P-CP) for DPC using multiple tests developed based on the extracted angular polarization signatures. Finally, P-CP algorithm is applied to the measurements of DPC and POLDER on 1 June 2008, and the analysis indicates that our cloud phase detection results agree well with the MODIS and POLDER cloud phase products.